THE USE OF YOUTUBE VIDEO TO IMPROVE THE SPEAKING SKILL OF GRADE XI STUDENTS AT SMK CLARENT KEFAMENANU - ratu, anggelina; Bouk, Edmundus; Kamlasi, Imanuel (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2021)
This study tends to identify whether the use of YouTube Video can improve students’ speaking skilland to measure to what extent YouTube Video can improve students’ speaking skill. The method used in this study is classroom action reserach. The research was conducted in two cycles. Every cycle consists of four steps; planning, action, observation, and reflection. The data collected were in the form of qualitative and quantitative. The qualitative data were gained through observation checklist, and questionnaire. While the quantitative data were obtained by conducting a test for cycle one and cycle two, and the data were in the forms of the students’ speaking scores.The results of this research showed that using YouTube video in the teaching and learning of speaking was proved to improve the students’ speaking skills. The students were more enthusiastic in learning speaking. They could actively involve in the speaking learning process. Moreover, the students were more confident and fluent in speaking practices. By comparing the total average scores of the students’ cycle one test and cycle two test, the researcher found that there was improvement from 41.5 to 61.4.